Biomechanical rationale for acetubalar component selection for total hip replacement in patients with dysplastic coxarthrosis - Loskutov, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Loss of anatomical shape of acetabulum under the dysplastic hip arthrosis, presence of defects and segmental bone deficiency in this area cause problems when choosing acetabular cup design. Objective: a comparative biomechanical evaluation of stability of pressing cup fixation and screw in terms of acetabulum segmental defect in patients with dysplastic coxarthrosis for arthroplasty. Methods: we developed a simplified geometric hexadecimal hip model with defects of segmental ter circuit 30°, 60°, 90° and 120°; and finite-element model of «bone – cup – insert – head implant» and estimated stress-strain distribution under axial load of 1000 N. Results: in the case of pressing cups and screw fixation, provided segmental defect up to 30°, the maximum stress in the bone bed is close to that of a healthy joint. This provides a higher quality cup screws initial stability. Given segmental defects of acetabulum 60°, 120° and 90° to reduce stress-strain distribution in bones must perform free plastic and bone screws to apply the cup. Use of pressing cups, with segmental defects over 60° is problematic. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> both types of fixing cup endoprosthesis provide stress-strain distribution similar to that of a healthy joint. The presence of segmental defect up to 30° did not significantly affect the stiffness and strength of the pelvic bone when using screws cup. Given the short-circuit defect 30° to 60° there is the threat of cracking. If the size of the defect exceeds 60°, significantly increases the risk of destruction circuit. Cup, pressed as compared to screws, moving under a static load of 1000 H.